From Abstract to Concrete: Associating the Users’ Tweets on “Success” - Fitria Fitria; Ajar Pradika Ananta Tur (Indonesian Journal of EFL and Linguistics, 2019)
By having Twitter for their interaction, users are demanded to express their idea in short-clear-easy to understand tweets. This condition pushes them to formulate every single word to conceptualize their idea as what happens to #success. They must build a tangible explanation of the idea of ‘success’ that is frequently determined by their life experience. This research is aiming to investigate how the users from the entire world associate their thinking about ‘success’. This research used the descriptive qualitative method by having tweets as the main data gained from Twitter during 2018. The data were analysed by using domain analysis attached to Conceptual Metaphor in Cognitive Semantics approach. The discoveries of this investigation are success is book, success is building, success is degree, success is food, success is gift, success is iceberg, success is journey, success is product, success is profession, success is trade, and success is money.